Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT “X” Kota Bangka Belitung - Fahria Az Zahra; Hardani Widhiastuti; Rusmalia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine and explain the workload, work stress and job satisfaction experienced by employees which can determine the success and progress of the company. Therefore, researchers tried to analyze the conditions of workload, work stress and job satisfaction applied in the company to determine the significant influence on employee performance. Judging from the occurrence of general phenomena that occur in companies. The research method used is quantitative with Partial Least Square (PLS). Data was collected through a questionnaire distributed to employees of PT